A Comparative Assessment Of Safety, Efficacy, And Cost-Effectiveness Of Glipizide-Metformin And Glimepiride-Metformin Combination Therapy In Type-2 Diabetes Mellitus - Amargeeth, Surendhar; Mathansekar, Reethika; C, Jagannath.; Jaishankar, Naveen; .G, Saipooja; Kannan, Visali; A. R, Periya Karuppan; Jebastine, M. Immanuel (Journal of Neonatal Surgery, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a common metabolic syndrome that needs effective long-term glycemic controls. There is wide usage of fixed-dose combinations (FDCs) of metformin with sulfonylureas. Glipizide metformin and glimepiride metformin are among them and these combinations are not effectively compared in terms of clinical and economic outcomes. Objectives: To compare the safety, efficacy and cost-effectiveness of glipizide metformin and glimepiride metformin fixed dose combination therapy in treating patients with T2DM. Methods: A prospective comparative study was done over a period of 6 months in a tertiary care hospital in Chennai on 200 T2DM patients. The patients were randomly grouped into Group A (glimepiride 2 mg + metformin 500 mg) and Group B (glipizide 5 mg + metformin 500 mg) and the efficacy was measured by the changes of fasting blood sugar (FBS), postprandial blood sugar (PPBS), random blood sugar (RBS) and HbA1c. The safety was evaluated with the Naranjo causality scale, whereas cost-effectiveness was determined as the cost per cent reduction in glycemic parameters. Results: Group A showed better glycemic control showing decreases in FBS (36.1%), PPBS (40.2%), RBS (30.1%), and HbA1c (16.8%) than Group B. The adverse drug reactions experienced in both groups were mild and similar. The overall therapy cost was a little higher in Group A but the cost per 1% glycemic reduction was more conducive pointing out to the better cost-effectiveness of the group. Conclusion: The glimepiride metformin combination therapy is more effective and cost-effective with an equal safety margin and should therefore be the choice of therapy in the long-term management of T2DM.